GRAded oral challenge for Drug allergy Evaluation—Delabelling described through families' voices. Issue 9 (20th July 2020) - Protudjer, Jennifer Lisa Penner; Golding, Michael; Bouwman, Tracy; Ben‐Shoshan, Moshe; Abrams, Elissa Michele
Abstract: Background: Children are often diagnosed with an antibiotic allergy, with little investigation to confirm whether it is a true allergy. Recent studies support the use of oral challenges to confirm antibiotic allergy. Yet, little is known about families' perceptions of these challenges, or experiences of living with a misdiagnosis, often for many years. Objective: To describe how families with a child previously labelled as "antibiotic allergic, " but who has subsequently been delabelled, perceive the experience of misdiagnosis and subsequent delabelling. Methods: We performed semi‐structured interviews with parents whose children had recently completed a graded oral challenge for antibiotic allergy. Interview transcripts were analysed concurrently, but independently, by two investigators, using content analysis. Results: A total of 15 parents (14 individual interviews; 1 mother‐father dyad) participated. Children were, on average, 5.04 ± 4.5 years and were first diagnosed in infancy (mean age: 1.82 ± 1.48 years) subsequent to a rash (14/14; 100%), and commonly at a walk‐in clinic (6/14; 42.9%). We identified four themes: (1) A red, raised rash results in a quick diagnosis despite a lack of testing, (2) sensitive care allays concerns, (3) delabelling brings relief, but also mystery and calls for proper diagnoses, and (4) quick diagnoses are reckless, but manageable through downward comparisons. Conclusion and Clinical Relevance: These findings underscore the importance of a careful physical examination and clinical history of the patient, but also an ongoing dialogue to support families, both of which would ideally begin at the time of initial investigation.